Activation of Rac1 GTPase promotes leukemia cell chemotherapy resistance, quiescence and niche interaction. Issue 5 (15th May 2013) - Wang, Ji-Ying; Yu, Pei; Chen, Shuying; Xing, Haiyan; Chen, Yirui; Wang, Min; Tang, Kejing; Tian, Zheng; Rao, Qing; Wang, Jianxiang
Abstract : Leukemia stem cells (LSCs) reside in bone marrow niche and receive important signals from the microenvironment that support self‐renewal, maintain quiescence and endow LSC with the ability of chemotherapy resistance. Rac1 belongs to the small GTP‐binding protein superfamily and is implicated in the interactions of hematopoietic progenitors and bone marrow niche. Our previous studies have shown that Rac1 is over‐expressed in leukemia patients and activation of Rac1 GTPase is closely associated with the efficient migration of leukemia cells. However, the potential functions for Rac1 GTPase in LSCs behaviors and in the residence of leukemia cells in niche remain unknown. In this study, by forced expression of a dominant‐negative form of Rac1 GTPase in a CD34+ myeloid leukemia cell line, as well as bone marrow cells from leukemia patients, we show that inactivation of Rac1 GTPase causes impaired migration and enhances chemotherapeutic sensitivity. Inactivation of Rac1 in leukemia cells also lead to a reduction in the frequency of cells in quiescent state and inhibition of homing to bone marrow niche. Gene expression analysis shows that inactivation of Rac1 down‐regulates the expression of several cell intrinsic cell cycle inhibitors such as p21, p27, and p57, as well as the extrinsic molecules that mediated the interaction of LSC with osteoblastic niche. Furthermore, we show that Rac1 mediated the localization in niche is further attributed to the maintenance of quiescence. Our results provide evidence for the critical role of Rac1 GTPase in leukemia cell chemotherapy resistance, quiescence maintenance and the interaction with bone marrow microenvironment. Highlights: Rac1 GTPase activation promotes migration and chemotherapy resistance in leukemia cells. The maintenance of quiescence in leukemia cells is preserved upon activation of Rac1 GTPase. Rac1 GTPase activation promotes leukemia cells homing to BM microenvironment and lodging in bone trabeculae region. Activation of Rac1‐GTPase up‐regulates quiescence intrinsic and extrinsic regulators. Osteoblastic cells promote active‐Rac1 enforced quiescence in leukemia cells.